2018
DOI: 10.1177/0018720817748145
|View full text |Cite
|
Sign up to set email alerts
|

Does Talking on a Cell Phone, With a Passenger, or Dialing Affect Driving Performance? An Updated Systematic Review and Meta-Analysis of Experimental Studies

Abstract: Objective An up-to-date meta-analysis of experimental research on talking and driving is needed to provide a comprehensive, empirical, and credible basis for policy, legislation, countermeasures, and future research. Background The effects of cell, mobile, and smart phone use on driving safety continues to be a contentious societal issue. Method All available studies that measured the effects of cell phone use on driving were identified through a variety of search methods and databases. A total of 93 studies c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(96 citation statements)
references
References 148 publications
(81 reference statements)
3
84
2
Order By: Relevance
“…The very low prevalence of cognitive disengagement in higher severity crashes also has implications for public policy. For example, existing research tends to conflate the risks of handheld and hands‐free cell phone conversations relative to cognitive disengagement (e.g., Young & Schreiner, ; National Safety Council, ; NHTSA, 2018; Caird, Simmons, Wiley, Johnston, & Horrey, ). Research has shown that there are meaningful differences between the risk of a handheld cell phone and well‐designed, integrated hands‐free cell phones.…”
Section: Discussionmentioning
confidence: 99%
“…The very low prevalence of cognitive disengagement in higher severity crashes also has implications for public policy. For example, existing research tends to conflate the risks of handheld and hands‐free cell phone conversations relative to cognitive disengagement (e.g., Young & Schreiner, ; National Safety Council, ; NHTSA, 2018; Caird, Simmons, Wiley, Johnston, & Horrey, ). Research has shown that there are meaningful differences between the risk of a handheld cell phone and well‐designed, integrated hands‐free cell phones.…”
Section: Discussionmentioning
confidence: 99%
“…Most individuals use a smartphone that contains a large number of potential “distractions” including games and the ability to readily short message (SMS) or interact with others through social media. Use of these devices can potentially affect the concentration of the user as well as others nearby particularly if the device is not set to silent mode or vibrates regularly . While the majority of colleagues would leave an MDT to answer a telephone call during the meeting, others might not be so polite.…”
Section: Distractions During a Mdtmentioning
confidence: 99%
“…While the majority of colleagues would leave an MDT to answer a telephone call during the meeting, others might not be so polite. By using a telephone at the same time as trying to do another task, performance is reduced . While this may not be crucial during an MDT, vital discussion could be missed as well as reducing the concentration of other team members .…”
Section: Distractions During a Mdtmentioning
confidence: 99%
See 2 more Smart Citations